Surgical management of spinal epidural abscess in elderly patients: a comparative analysis between patients 65-79 years and ≥80 years with 3-year follow-up - Lenga, Pavlina; Gülec, Gelo; Bajwa, Awais Akbar; Issa, Mohammed; Kiening, Karl; Unterberg, Andreas; Ishak, Basem (World neurosurgery, 2022)
Recently, the incidence of pyogenic vertebral osteomyelitis with spinal epidural abscess (SEA) has increased. However, the most appropriate surgical management remains debatable, especially for older patients. This study aimed to compare the clinical course in older patients aged between 65 and 79 years and those 80 years or older undergoing surgery for SEA.